The role of piperacillin/tazobactam in the treatment of Hidradenitis suppurativa - Aviv Barzilai; Shir Toubiana; Adam Dalal; Sharon Baum (Journal of Dermatological Treatment)
Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease. Most patients with moderate-to-severe disease require long-term antibiotic treatment, or biologic treatments to control their disease. Despite these interventions, relapses are common. This study evaluated the effectiveness of piperacillin/tazobactam treatment in patients with Hurley stage II and III HS who experienced disease flares and did not respond to conventional antibiotic and biologic treatment. Methods: Patients with HS hospitalized at the Department of Dermatology, Sheba Medical Center between August 2021 and January 2023 were retrospectively analyzed. Results: A cohort of ten such patients were treated with piperacillin/tazobactam for 6–21 days. Eight (80%) and two (20%) patients respectively demonstrated 2- and 1-grade improvements, from their baseline HS-Physician Global Assessment score. During the follow-up period, nine patients were monitored. HS Clinical Response (HiSCR) was achieved in six (66.7%) and five (55.6%) patients at the 3- and 6-month follow-up visits, respectively. Conclusions: In conclusion, Piperacillin/tazobactam emerges as a promising therapeutic option for disease flare-up in patients with Hurley stage II and III HS who do not respond to conventional treatment. Thus, piperacillin/tazobactam should be considered as crisis therapy for this patient subset.